2011
DOI: 10.1111/j.1471-4159.2011.07273.x
|View full text |Cite
|
Sign up to set email alerts
|

CaMKII activation is a novel effector of alcohol’s neurotoxicity in neural crest stem/progenitor cells

Abstract: Prenatal ethanol exposure causes significant neurodevelopmental deficits through its induction of apoptosis in neuronal progenitors including the neural crest. Using an established chick embryo model, we previously showed that clinically relevant ethanol concentrations cause neural crest apoptosis through mobilization of an intracellular calcium transient. How the calcium transient initiates this cell death is unknown. Here we identify CaMKII as the calcium target responsible for ethanol-induced apoptosis. Imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 68 publications
(138 reference statements)
3
59
0
Order By: Relevance
“…Although little is known about the role in alcohol addiction, alcohol affects CaMKII levels in the brain (Smith and Navratilova, 1999;McBride et al, 2009;Mahadev et al, 2001;Lee et al, 2011) and increases phosphorylation rate at Thr286 (Garic et al, 2011;Wang et al, 2012). Both may control alcohol effects on cellular signaling (Liu et al, 2006;Xu et al, 2008), behavior (Kim et al, 2012;Wang et al, 2012), and neurotoxicity (Garic et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although little is known about the role in alcohol addiction, alcohol affects CaMKII levels in the brain (Smith and Navratilova, 1999;McBride et al, 2009;Mahadev et al, 2001;Lee et al, 2011) and increases phosphorylation rate at Thr286 (Garic et al, 2011;Wang et al, 2012). Both may control alcohol effects on cellular signaling (Liu et al, 2006;Xu et al, 2008), behavior (Kim et al, 2012;Wang et al, 2012), and neurotoxicity (Garic et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies showed that CaMKIIs play an important role in cell apoptosis. They also reported that CaMKII, as a critical mediator of ethanolinduced apoptosis, switches to convert ethanol's short-lived Ca 2+ transient into a long-term effect on cellular activity (Garic et al 2011). Some study results indicate that CaMKII does not participate in the extrinsic cascade of apoptosis but is involved in the intrinsic (mitochondrial) pathway.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, repeated alcohol administration enhances CaMKII activity in neurons and astrocytes ( Figure 1) [108,109] and increases phosphorylation rate [110]. Free choice alcohol drinking increased protein levels of CaMKII, but not CaMKII in the amygdala and NAc of mice [111].…”
Section: Alcoholmentioning
confidence: 98%